Cover, Content, and Editorial Note from Borneo J Pharm Vol. 9 No. 2 June 2026 - Mohammad Rizki Fadhil Pratama (Borneo Journal of Pharmacy, 2026)
Assalamu'alaikum Wr. Wb. Alhamdulillahirabbil 'alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm) has been published in June 2026. This edition contains twelve articles spanning: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutics, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, Community Pharmacy, and Clinical Pharmacy Practice. This edition includes writings from three countries: Indonesia, Malaysia, and South Korea.The editorial board is fully aware that there is still room for improvement in this edition; hence, with all humility, we are willing to accept constructive suggestions and feedback to improve the publication in future editions. The editorial board would like to thank all editors, reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, will participate again in the publication of the next edition, scheduled for September 2026. Wassalamu'alaikum Wr. Wb. Palangka Raya, June 2026 Editor-in-Chief